(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
This research was carried out during the years 2015 and 2016. Fifteen phenotypes of olive (Olea europaea L.) belonging to Khdairy variety were collected from 5 sites in Lattakia (Bouka, Mashkita, Ein albaida, Alkanjra and Jannata). The study included 29 morphological traits, 26 of them were identified by the International Olive Council (IOC), in particular the general Specifications of the tree, leaf, inflorescence and fruit, in addition to some characteristics of the stone, which is one of the most important morphological characterization criteria. In addition, three traits (Not included in IOC) were added to this study, the internode length of the fruiting shoots, as well as the leaf surface and thickness. Results based on morphological data were used to establish a dendrogram showing the relationship between all phenotypes analyzed in this study. The dendrogram showed morphological differences among Khdairy phenotypes reached (36%). Variations between phenotypes of the same site were detected, and the highest percentage (20%) was revealed between phenotypes of Mashkita site (SN). Variation between phenotypes of one site didn’t found in some cases (BC1& BC2, SN2&SN3) The variation shown between some phenotypes for qualitative characteristics leads to the thought of existence of genetic variation among the studied olive phenotypes, which represent a high importance especially in the field of breeding and genetic improvement of cultivated olives. نفذ البحث خلال الموسمين 2015 و2016 على 15 طرازاً من الزيتونOlea europaea L. ، يتبعون لصنف الخضيري، موجودة في خمسة مواقع من محافظة اللاذقية (بوقا، مشقيتا، عين البيضا، القنجرة، جناتا). تناولت الدراسة29 صفة مظهرية، حدد منها المجلس الدولي للزيتون (International Olive Council) "IOC" /26/ صفة خاصة بالشكل العام للشجرة والورقة والعنقود الزهري والثمرة إضافة لبعض الصفات الخاصة بالنواة والتي تعتبر من أهم معايير التوصيف المظهري . تم إدراج ثلاثة معايير خاصة بهذه الدراسة، بالإضافة إلى المعايير السابقة، وهي طول السلاميات للفروع الثمرية إضافة إلى صفتي مساحة وسماكة الورقة حيث تم وضع مقاييس خاصة بهذه الصفات لدى طرز صنف "الخضيري" المدروسة. تم تحليل القراءات المأخوذة للصفات المختارة، واستخدمت نتائجها في تحديد ورسم مخطط شجرة القرابة بين طرز صنف الخضيري. أظهر المخطط وجود اختلافاً بين الطرز المدروسة وصلت نسبته لـ (36%). ظهرت أعلى نسبة تباين ضمن طرز الموقع الواحد (20%) بين طرز موقع مشقيتا (السنديانة)، في حين غاب التباين عند بعض طرز الموقع الواحد (BC1 و BC2, SN2 و SN3). يقود التباين في بعض الصفات النوعية التي تضمنتها الدراسة للاعتقاد بوجود تباين وراثي بين طرز الزيتون المدروسة وهذا يكسب الطرز المتميزة منها أهمية خاصة في مجال التربية والتحسين الوراثي للزيتون المزروع.